TECHNOLOGIES AND ALGORITHMS FOR USING ARTIFICIAL INTELLIGENCE IN EDUCATION (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
The development of artificial intelligence (AI) and its implementation in the field of education is becoming widespread. Experts agree that AI will lead to significant transformations in industries related to intellectual activity, which include education.